2015
DOI: 10.14814/phy2.12412
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p53 in NIH3T3 mouse fibroblasts following hyperosmotic stress

Abstract: The aim of this project was to analyze the regulation of p53 expression in NIH3T3 fibroblasts under the influence of increasing hyperosmotic stress. Expression of p53 showed a biphasic response pattern in NIH3T3 cells under increasing osmotic stress (337 mOsm to 737 mOsm) with a maximum at 587 mOsm. Under isotonic conditions p53 expression increased after addition of the proteasome inhibitor MG132 indicating that cellular p53 levels in unperturbed cells is kept low by proteasomal degradation. However, under hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…It has previously been shown that acute hyperosmotic stress leads to a biphasic stabilization and activation of the transcription factor p53 in mouse NIH3T3 fibroblasts, supposedly through Ser-15 phosphorylation of p53 by the serine/threonine kinase ATM and/or the p38 MAP kinase ( 11 , 27 ). As exposure to Cisplatin likewise elicits cell shrinkage under isotonic conditions, we tested the effect of Cisplatin on p53-mediated signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that acute hyperosmotic stress leads to a biphasic stabilization and activation of the transcription factor p53 in mouse NIH3T3 fibroblasts, supposedly through Ser-15 phosphorylation of p53 by the serine/threonine kinase ATM and/or the p38 MAP kinase ( 11 , 27 ). As exposure to Cisplatin likewise elicits cell shrinkage under isotonic conditions, we tested the effect of Cisplatin on p53-mediated signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Planells-Cases and coworkers ( 36 ) indicate that Cisplatin induced taurine release and the cytotoxic effects of the chemotherapeutic drugs Staurosporine, Cisplatin and Carboplatin are abolished in LRRC8A and LRRC8D knockout HEK cells ( 36 ). In this context it is noted that osmotic cell shrinkage previously has been shown to induce Caspase-3 activation and apoptosis in EATC via activation of a volume sensory cell death pathway, where p53 is phosphorylated by the protein kinase p38 and hence protected against degradation ( 11 , 27 ). Consequently, it has been suggested that Cisplatin-induced cell death in A2780WT cells via the intrinsic cell death pathway involves activation of the volume sensory cell death pathway due to activation of transporters for ions/organic osmolytes/AVD ( 37 ) and that the reduced Cisplatin sensitivity in A2780CisR partly reflects reduced LRRC8A expression/AVD ( 44 ).…”
mentioning
confidence: 99%
“…For the first time, unsupervised analysis of RNaseq data suggested a role for HTS treatment in the modulation of the p53-p21 signaling axis, as we further confirmed through RT-PCR, WB, and fluorescence microscopy. Of note, hyperosmolarity has been very recently associated with increased p53 protein expression in mouse fibroblasts, 28 where p53 protein was stabilized through a post-translational mechanism (phosphorylation at serine 15), decreasing its degradation via MDM2-mediated ubiquitinylation. Here, similar results were observed because RNaseq and proteomics data showed increased transcription and protein expression of genes downstream to p53, above all p21, while only protein levels of p53 (but not its direct mRNA transcription) were significantly up-regulated by HTS alone.…”
Section: Discussionmentioning
confidence: 99%
“…Given that only if osmolarity change due to taurine administration was more than 737 mOsm, cell viability altered significantly, we did not carried on experiments in equimolar sucrose or similar osmolyte as control [30,31]. According to the results from a CCK-8 assay, fibroblasts treated with up to 100 mM taurine for 48 h exhibited no significant reduction of cell viability (Fig.…”
Section: Taurine Had No Significant Effect On Cell Apoptosismentioning
confidence: 99%